Capacity building for the disability task force through therapeutic communication training in Geger Subdistrict - Wahyuningsih, Sri; Indarto, Cahyo; Rozi, Fachrur; Janah, Laila Miftahul; Azhari, Arislawati Lintang; Aulia, Meyshinta (Community Empowerment, 2025)
Mental health and disability are crucial issues that directly impact the quality of life in society. The Mental and Physical Disability Task Force of Geger Subdistrict plays a strategic role as patient companions; however, they still face challenges due to limited therapeutic communication skills. This community service project aims to enhance the capacity of the task force through socialization, interactive discussions, and practical simulations. Program evaluation was conducted through needs observation and monitoring throughout the implementation. Results showed a significant increase in the task force's knowledge regarding the principles of empathy, feeling validation, and active listening, as well as the mastery of techniques for managing hallucinations and delusions. Furthermore, there were positive behavioral changes, including increased confidence, patience, and composure when dealing with patients. This training proved effective in strengthening the role of the task force as social change agents to create an inclusive, supportive, and stigma-free community environment for individuals with both mental and physical disabilities.